Comparative study on web-based and cloud-based application. Issue 7 (2nd October 2020) - Tandon, Anisha; Madan, Mamta; Dave, Meenu
Abstract: Software Testing is a demanding activity for several software engineering projects and is one of the prime technical part of the software engineering cycle that still contains considerable challenges. Testing software requires enough resources and budget to complete it successfully. This paper proposed a Traceability Matrix for Web-based and Cloud-based Applications. This research introduced a new matrix that contains features of both Traceability and Test Coverage Matrix and after the development of that Matrix, the same is first implemented in the web-based application and then further enhancement of the same is implemented in a cloud-based application. This research paper also presented a comparative study on Web-based and Cloud-based Applications.